If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -3 = 3x + 33 Reorder the terms: -3 + -1x = 3x + 33 Reorder the terms: -3 + -1x = 33 + 3x Solving -3 + -1x = 33 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -3 + -1x + -3x = 33 + 3x + -3x Combine like terms: -1x + -3x = -4x -3 + -4x = 33 + 3x + -3x Combine like terms: 3x + -3x = 0 -3 + -4x = 33 + 0 -3 + -4x = 33 Add '3' to each side of the equation. -3 + 3 + -4x = 33 + 3 Combine like terms: -3 + 3 = 0 0 + -4x = 33 + 3 -4x = 33 + 3 Combine like terms: 33 + 3 = 36 -4x = 36 Divide each side by '-4'. x = -9 Simplifying x = -9
| (8m-8n)(4m-7n)= | | 8x+7x-88=110-7x | | -3x-(-5)+2x=-x-4 | | 1+5x-40=1x-5 | | x+x+4=36 | | -10+x+4-4-5=7x-5 | | 6x+2(7x-4)=92 | | x+2y=29 | | -3x+8=18+4x | | x+2x=62 | | x-3(x-4)+2=14-3(5x+6) | | 3*n-8=2*n+15 | | 4(6x+3x)=12 | | 60k+60k=50k+100 | | x+x+2=62 | | -9+2.5y-.7y+1+6.4y= | | 2.4x=4x-88 | | X^2+5x=46 | | xy-d=mfory | | -18+9x=63 | | 2(x+4)+3(-x)=2(-x) | | -x+1=3x+21 | | 6X-1Y=18 | | 2(4c-1)=8c-2 | | x-2x-3=-x+9 | | 2s+8=22 | | 3(5x-4)-8x=7x-12 | | -7x+14=49-2x | | 10y+8x=314 | | 5y-3=2y-6 | | 4v-12-7v=6-2v | | 2x+5yx+y=3 |